THE EFFECT OF YOGA ON SLEEP QUALITY AND INSOMNIA IN WOMEN WITH SLEEP PROBLEMS : A SYSTEMATIC REVIEW - Nugraheni, Artha Investari; Rahmah, Dini Amelia; Agus Prastyo, Wahyu; Azhari, Ririn; Merisa L, Bella; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: With prevalence estimates ranging from 4% to over 20% of the adult population, insomnia is the most prevalent sleep complaint and a serious public health problem. Yoga has also been utilized therapeutically since it is thought that various styles of yoga might have distinct psychophysiological effects. Aims : This systematic review is to review the effect of yoga on sleep quality and insomnia in women with sleep problem. Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 33 articles, whereas the results of our search on SAGEPUB brought up 416 articles, our search on SCIENCE DIRECT brought up 1107 articles. The results of the search conducted for the last year of 2014 yielded a total 26 articles for PubMed, 265 articles for SAGEPUB and 684 articles for SCIENCE DIRECT. In the end, we compiled a total of 7 papers, 4 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included seven research that met the criteria. Conclusion: In summary, when compared to non-active control settings, yoga intervention can help women manage their sleep issues in either pregnant women, worker, or women with disease.